THE INFLUENCE OF INCREASED PRICES OF SATISFACTIONS ON ECONOMIC GROWTH - Cita Ayni Putri Silalahi; Suaidah Suaidah; Alistraja Dison Silalahi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Economic growth greatly affects people's purchasing power of basic commodities. The phenomenon that occurred entering the beginning of September 2022 the prices of a number of basic commodities were observed to have increased. There are several prices of basic commodities that have increased. The purpose of this study is to analyze the increase in staple commodities such as premium rice, eggs, garlic, red chili peppers, sugar, and cooking oil together whether there is a significant effect on economic growth in Indonesia using multiple linear regression analysis. In this study used primary data, with simple random sampling as a sampling technique. Hypothesis testing using the F test is known that the commodities of premium rice, eggs, garlic, red cayenne pepper, sugar, and cooking oil and the number of family members together have influence on economic growth in Indonesia. The variables that have a significant influence on the income of coconut farmers are the amount of coconut production and the cost and the resulting coefficient value is 0.756 or 75.6% percent.